Different pathways toward net-zero emissions imply diverging health impacts: a health impact assessment study for France - Léo Moutet; Aurélien Bigo; Philippe Quirion; Laura Temime; Kévin Jean (IOP Publishing, 2024)
In the transport sector, efforts to achieve carbon neutrality may generate public health co-benefits by promoting physical activity. This study aims to quantify the health impacts related to active transport based on four different scenarios leading France toward carbon neutrality in 2050. The French Agency for Ecological Transition developed four consistent and contrasting scenarios (S1 to S4) achieving carbon neutrality by 2050 as well as a business-as-usual (BAU) scenario that extends our current lifestyles until 2050, without reaching net-zero. For each of these Transitions2050 scenarios, we distributed the mobility demand for walking, cycling and e-cycling across age groups. Relying on the health impact assessment framework, we quantified the impacts of the corresponding physical activity on all-cause mortality. The impact of each of the carbon neutrality scenarios was determined by comparison with estimates from the BAU scenario. In S1 and S2 scenarios, volumes of active transport are projected to increase to fulfill the World Health Organizations (WHO) recommendations by 2050, while they increase slightly in S3 and decrease in S4. S2 scenario reaches the highest levels of health co-benefits, with 494 000 deaths prevented between 2021 and 2050. This would translate into a life expectancy gain of 3.0 months for the general population in 2050, mainly driven by e-bikes. S1 would provide smaller but important health benefits, while these benefits would be modest for S3. On the contrary, S4 implies 52 000 additional deaths as compared to the BAU scenario and a loss of 0.2 month in life expectancy. Different ways to decarbonize mobility in a net-zero perspective may achieve very contrasting public health co-benefits. This study illustrates how the public health dimension may provide a relevant insight in choices of collective transformation toward net-zero societies.